Some aspects of ecological engineering in modern heating systems of cities - Letyagina, Ekaterina (IOP conference series. Earth and environmental science, 2021)
This article outlines the results of a study of some aspects of implementation and use of ecological engineering elements in the heat supply systems of large urban agglomerations of the Russian Federation. It considers important problems associated with the definition of the term ecological engineering, defines the elements of ecological engineering that can be introduced into the sphere of heat supply of large urban agglomerations. It provides the data on heat energy losses in some subjects of the Russian Federation with harsh climatic conditions, in which heat supply to the large cities lasts for over 9 months a year. The article also identifies the main challenges the heat supply systems used in large metropolitan agglomerations of the Russian Federation face related to the modernization and digital transformation of the heat supply sector of Russian cities. It designates the main problems and opportunities of ecological engineering, which will allow, if widely implemented, providing remote control of the operation of district heating systems, controlling their temperature regime and pressure in pipelines, carrying out the necessary engineering calculations of the functioning of the systems relative to the topography of a particular urban agglomeration. In addition, the study outlines important components of the digitalization of district heating systems in cities to ensure their efficient, effective and, most importantly, safe for the ecosystems of large urban agglomerations, functioning. It has been established that ecological engineering in the district heating industry of large urban agglomerations has to be directed at conservation and restoration of the reserves of natural thermal resources, as well as the natural environment as a whole, by reducing the intensity of operation and emissions into the atmosphere that are produced during the processing of fuel resources.